FABRIC ART: REPORT OF A SUCCESSFUL PRACTICE IN SPECIAL EDUCATION - Nascimento, Francisca Raquel Santos; Damasceno, Geslaine Barbosa (Seven Editora, 2025)
This article describes a pedagogical practice carried out in the Multifunctional Resource Room (SRM) of the Capitão Silvio de Farias State Full-Time High School in Rondônia, aimed at students with special needs. The activity consisted of creating a toiletry bag using cutting and sewing techniques, with the goal of promoting the development of motor, cognitive, social, and emotional skills. Analysis of the results, based on theoretical frameworks on integrative methodologies and inclusive education, revealed significant improvements in the participants’ autonomy, motor coordination, and social interaction, reinforcing the importance of manual practices in the inclusive educational process. DOI: https://doi.org/10.56238/sevened2025.036-014